REGULATION OF ACIDIC AND BASIC TYPES OF PROTEINS OF A TELEOST TIL API A MOSSAMBICA UNDER SUBLETHAL MALATHION IMPACT - Sahib, I Kabeer Ahammad; Rao, K Siva Prasada; Rao, K R S Sambasiva; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
During the course of malathion (2mg/l) exposure, the sucrose-soluble proteinsand insoluble proteins increased considerably in muscle, gill and liver tissuesthroughout the time course study. The acidic and basic types of protein alsoshowed an increase in muscle, gill and liver tissues. With some exception, in all the time intervals, the basic type of protein was relatively higher than the acidictype of protein leading to basic intracellular enviornment. In spite of less effectivenessof malathion in basic environment, the higher levels of basic proteins maypartially contribute towards detoxification. It is likely that an effective bufferingpotential may exist in the malathion exposed fishes, probably regulated by controlledsynthesis of acidic and basic types of protein